E and prM proteins of genotype V Japanese encephalitis virus are required for its increased virulence in mice. Issue 11 (November 2019) - Tajima, Shigeru; Shibasaki, Ken-ichi; Taniguchi, Satoshi; Nakayama, Eri; Maeki, Takahiro; Lim, Chang-Kweng; Saijo, Masayuki
Abstract: We previously showed that the Japanese encephalitis virus (JEV) genotype V (GV) strain Muar exhibits significantly higher virulence in mice than the genotype I (GI) JEV strain Mie/41/2002. In this study, we attempted to identify the region responsible for the increased virulence of GV JEV using recombinant intertypic and single mutant JEVs. Intertypic viruses containing the GV E region in the Mie/41/2002 backbone showed increased pathogenicity in mice. The amino acid at position 123 in the E protein (E123) of the Mie/41/2002 and GV JEVs was serine and histidine, respectively. A serine-to-histidine substitution at E123 of the Mie/41/2002 increased its virulence. However, histidine-to-serine changes at E123 in the intertypic mutants with the GV E region remained highly virulent. GV Muar prM-bearing mutants were also highly pathogenic in mice. Our results suggest that the E and prM proteins of GV JEV are responsible for the highly virulent characteristics of GV JEV. Abstract : Genetics; Microbiology; Virology; Japanese encephalitis virus; Genotype V; E protein; prM protein; Pathogenicity; Reverse genetics; Infectious cDNA clone